Health Impact and Cost-Effectiveness of HIV Testing, Linkage, and Early Antiretroviral Treatment in the Botswana Combination Prevention Project. (1st August 2022) - Resch, Stephen C.; Foote, Julia H. A.; Wirth, Kathleen E.; Lasry, Arielle; Scott, Justine A.; Moore, Janet; Shebl, Fatma M.; Gaolathe, Tendani; Feser, Mary K.; Lebelonyane, Refeletswe; Hyle, Emily P.; Mmalane, Mompati O.; et al.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Background: The Botswana Combination Prevention Project tested the impact of combination prevention (CP) on HIV incidence in a community-randomized trial. Each trial arm had ∼55, 000 people, 26% HIV prevalence, and 72% baseline ART coverage. Results showed intensive testing and linkage campaigns, expanded antiretroviral treatment (ART), and voluntary male medical circumcision referrals increased coverage and decreased incidence over ∼29 months of follow-up. We projected lifetime clinical impact and cost-effectiveness of CP in this population. Setting: Rural and periurban communities in Botswana. Methods: We used the Cost-Effectiveness of Preventing AIDS Complications model to estimate lifetime health impact and cost of (1) earlier ART initiation and (2) averting an HIV infection, which we applied to incremental ART initiations and averted infections calculated from trial data. We determined the incremental cost-effectiveness ratio [US$/quality-adjusted life-years (QALY)] for CP vs. standard of care. Results: In CP, 1418 additional people with HIV initiated ART and an additional 304 infections were averted. For each additional person started on ART, life expectancy increased 0.90 QALYs and care costs increased by $869. For each infection averted, life expectancy increased 2.43 QALYs with $9200 in care costs saved. With CP, an additional $1.7 million were spent on prevention and $1.2 million on earlier treatment. These costs were mostly offset by decreased care costs from averted infections, resulting in an incremental cost-effectiveness ratio of $79 per QALY. Conclusions: Enhanced HIV testing, linkage, and early ART initiation improve life expectancy, reduce transmission, and can be cost-effective or cost-saving in settings like Botswana.